2021
DOI: 10.3390/en14227546
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Insulation Materials for Facades: Analyzing Detachments Using Numerical Simulations and Infrared Thermography

Abstract: In building construction, it is very important to reduce energy consumption and provide thermal comfort. In this regard, defects in insulating panels can compromise the capability of these panels of reducing the heat flow by conduction with the surroundings. In recent years, both experimental techniques and numerical methods have been used for investigating the effect of defects on the thermal behavior of building panels. The main novelty of this work regards the application of both numerical and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Earlier investigations showed that numerical simulation can eliminate the influence of uneven heating, environmental interference, and other factors on the surface temperature of the cable [23], which is conducive to the analysis of the heat transfer phenomenon of the cable and provides a theoretical basis for the experimental analysis. Commercial finite element analysis software was used to calculate the surface temperature field of the cable insulation under the halogen lamp heating, and the influence of insulation defects on the surface temperature field was analyzed.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Earlier investigations showed that numerical simulation can eliminate the influence of uneven heating, environmental interference, and other factors on the surface temperature of the cable [23], which is conducive to the analysis of the heat transfer phenomenon of the cable and provides a theoretical basis for the experimental analysis. Commercial finite element analysis software was used to calculate the surface temperature field of the cable insulation under the halogen lamp heating, and the influence of insulation defects on the surface temperature field was analyzed.…”
Section: Numerical Simulationmentioning
confidence: 99%